Co-movement and the transmission of the Japanese REIT market in different property sectors: a comparative analysis of different monetary policy regimes. (2018) - Ito, Takayasu
Three REIT markets in different property sectors do not co-move before the introduction of aggressive monetary policies in Japan. REIT market was sluggish after the impacts of the Lehman shock and the Great East Japan Earthquake. They move almost independently with just a few mutual transmissions. At the same time, monetary policies were not as powerful as in the period of Abenomics. On the other hand, with the introduction of strong monetary policies, REIT market became bullish. Aggressive monetary policies, as a common factor, play important roles in the co-movement and mutual transmission of three REIT markets in different property sectors. In other words, three REIT markets in different property sectors are formed through mutual dependence and influence. The results of this paper imply that large scale easing policies contribute to mitigating asset deflation by increasing the prices of Japanese REIT market.